(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study’s objective is to better understand the causes, symptoms, classifications, and treatment options for mandible fractures, with a focus on condylar and subcondylar fractures. The patient’s age, the kind of fracture, the patient’s systemic state, any previous fractures, the teeth, the likelihood It is important to consider the presence of foreign materials, the extent of occlusal restoration by intermaxillary fixation, and other factors before making a treatment decision.